2018
DOI: 10.3389/fncel.2018.00388
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Governing the Stem Cell’s Fate in Brain Cancer: Factors of Stemness and Quiescence

Abstract: Cellular quiescence is a reversible, non-cycling state controlled by epigenetic, transcriptional and niche-associated molecular factors. Quiescence is a condition where molecular signaling pathways maintain the poised cell-cycle state whilst enabling rapid cell cycle re-entry. To achieve therapeutic breakthroughs in oncology it is crucial to decipher these molecular mechanisms employed by the cancerous milieu to control, maintain and gear stem cells towards re-activation. Cancer stem-like cells (CSCs) have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 186 publications
(199 reference statements)
2
28
0
Order By: Relevance
“…We also further characterized the CSCs by comparing different cell cycle stages of adherent cells with secondary spheres as a measure of cellular quiescence, a signature of CSCs. It is well established that CSCs are maintained in a poised, quiescent state characterized by slow cell cycling that confers them resistance to cytotoxic drugs (19,20). Supporting our hypothesis, secondary spheres showed significantly higher percentages of G 0 -G 1 population than the adherent cells ( fig.…”
Section: Smar1 Expression Is Attenuated In Cscssupporting
confidence: 82%
“…We also further characterized the CSCs by comparing different cell cycle stages of adherent cells with secondary spheres as a measure of cellular quiescence, a signature of CSCs. It is well established that CSCs are maintained in a poised, quiescent state characterized by slow cell cycling that confers them resistance to cytotoxic drugs (19,20). Supporting our hypothesis, secondary spheres showed significantly higher percentages of G 0 -G 1 population than the adherent cells ( fig.…”
Section: Smar1 Expression Is Attenuated In Cscssupporting
confidence: 82%
“…In contrast, FBS reduced the expression of stem markers (Oct3/4, SOX2, Nestin, Musashi-1, PDGFRα, Notch2, Nanog, STAT3, c-Myc and CD49f) in GSLCs. These results are consistent with retinoic-acid induced changes in differentiation and stem markers in GSLCs [ 13 ]. Among the 18 stem cell markers we tested, significant differences between GSLC and differentiated cells were observed in the expressions of Oct3/4, SOX2, Nestin, PDGFRα, Nanog and STAT3 in both no.…”
Section: Discussionsupporting
confidence: 88%
“…A previous study that investigated the impact of CD98 on stemness, proliferation and cell survival in acute myelogenous leukemia showed that loss of CD98 triggers apoptosis and depletion of acute myelogenous leukemia stem cells and CD98-mediated adhesion to vasculature promotes leukemia stem cell maintenance [ 28 ]. The vascular niche is one of the important GSCs niches that sustain stemness and resistance to chemoradiation therapy [ 12 , 13 ]. We speculate that GSCs with CD98 expression that reside in the vascular niche can take up BPA through LAT1 in a heterodimeric complex with CD98 on the plasma membrane and can be targeted by BNCT as our data show.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][22][23] Some have interpreted glioma recurrence as evidence that quiescent "glioma stem cells" persist in a quiescent state after chemoradiation prior to ultimately re-initiating tumor recurrence. [24] Other evidence in glioma and other tumors supports induction of a senescent-like state, after cytotoxic therapy. If indeed quiescent glioma stem cells and senescent cells both exist in glioma after standard therapy, do they both actively coexist in parallel at all points following therapy, or could initially senescent cells escape senescence to revitalize the tumor as quiescent stem cells?…”
Section: Discussionmentioning
confidence: 98%